Management of infectious in immunocompromised patients - Glauser, Michel-Pierre; Pizzo, Philip A (Saunders, 2000)
This book provides a practical and clinically useful source of information to all those who deal with immunocompromised patients on a day to day basis. This concise guide covers the most commonly asked questions about diagnosis, treatment, and prevention of infections of the immunocompromised patient.
Keywords: imunita; Immunity; Transplantation Immunology; imunokompromitovaný pacient; syndromy imunologické nedostatečnosti; Infection Control; Immunocompromised Host; transplantační imunologie; Immunologic Deficiency Syndromes; kontrola infekce; infekční lékařství; infekce; Infections; alergologie a imunologie